Dysbiotic Gut Microbiota and Dysregulation of Cytokine Profile in Children and Teens With Autism Spectrum Disorder - Cao, Xia; Liu, Kevin; Liu, Jun; Liu, Yen-Wenn; Xu, Li; Wang, Hua; Zhu, Yunhui; Wang, Pengfei; Li, Zhiwei; Wen, Jie; Shen, Chen; Li, Meng; et al. (Frontiers in Neuroscience, 2021)
Inflammation and the gut-brain axis have been implicated in the pathogenesis of Autism spectrum disorders (ASDs). To further understand the relationship between aberrant immune responses and dysbiotic features of the gut microbiome in ASD, we enrolled 45 ASD individuals and 41 healthy control subjects with ages ranging from 2-19 years. We found that ASD group subjects have significantly higher plasma levels of IL-2, IL-4, IL-5, IL-6, IL-10, TNF-α, TNF-β, and IFN-γ when compared to healthy controls (FDR-adjusted P < 0.05). The plasma levels of pro-inflammatory cytokines IFN-γ and IL-6 are found to be further associated with several largely pathogenic gut microbiota uniquely detected in subjects with ASD. Furthermore, the ASD gut microbiome is characterized by reduced levels of several beneficial microbiota, including Bacteroides (FDR-adjusted P < 0.01) and Lachnospiraceae (FDR-adjusted P < 0.001). Analysis of Lachnospiraceae family and genus level taxa suggested that relative abundances of such taxa are negatively correlated with pro-inflammatory signaling cytokines IFN-γ and IL-6, particularly in subjects with severe ASD as defined by CARS (P < 0.05). Several largely pathogenic genera are determined to be associated with the pro-inflammatory cytokines IFN-γ and IL-6 (FDR-adjusted P < 0.1). Additionally, IL-4 is significantly negatively correlated with CARS total score (P < 0.05). Based on such results, we propose that the association between the disturbances of specific cytokines and alterations in gut microbiota abundance observed in children and adolescents with ASD provides additional evidence on the induction of aberrant pro-inflammatory mechanisms in ASD and its early diagnosis.